iOTA: An Approach to Secure Over-The-Air Updates on the Internet of Things Scenario - Peter, Cleber S.; Oliveira, Thayná; Monks, Eduardo M.; Motta, Fernanda P.; Barbosa, Jorge L. V.; Yamin, Adenauer C. Yamin (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2021: Proceedings of the 27th Brazilian Symposium on Multimedia and the Web, 2021)
The IoT's widely distributed nature has promoted demands for Over-The-Air (OTA) upgrading of embedded systems. This paper presents the conception of a new approach, called iOTA, which meets the security requirements of the SUIT specification of the Internet Engineering Task Force (IETF). The partial evaluation of the proposal points to the continuation of the research and showed that iOTA stands out in terms of security in relation to the other approaches proposed by the literature, offering protection against attacks to which a remote update of an embedded system is usually exposed.